Photoperiod and rainfall are associated with seasonal shifts in social structure in a songbird. (23rd December 2022) - Welklin, Joseph F; Lantz, Samantha M; Khalil, Sarah; Moody, Nicole M; Karubian, Jordan; Webster, Michael S
Abstract: Seasonally breeding animals often exhibit different social structures during non-breeding and breeding periods that coincide with seasonal environmental variation and resource abundance. However, we know little about the environmental factors associated with when seasonal shifts in social structure occur. This lack of knowledge contrasts with our well-defined knowledge of the environmental cues that trigger a shift to breeding physiology in seasonally breeding species. Here, we identified some of the main environmental factors associated with seasonal shifts in social structure and initiation of breeding in the red-backed fairywren ( Malurus melanocephalus ), an Australian songbird. Social network analyses revealed that social groups, which are highly territorial during the breeding season, interact in social "communities" on larger home ranges during the non-breeding season. Encounter rates among non-breeding groups were related to photoperiod and rainfall, with shifting photoperiod and increased rainfall associated with a shift toward territorial breeding social structure characterized by reductions in home range size and fewer encounters among non-breeding social groups. Similarly, onset of breeding was highly seasonal and was also associated with non-breeding season rainfall, with greater rainfall leading to earlier breeding. These findings reveal that for some species, the environmental factors associated with the timing of shifts in social structure across seasonal boundaries can be similar to those that determine timing of breeding. This study increases our understanding of the environmental factors associated with seasonal variation in social structure and how the timing of these shifts may respond to changing climates. Abstract : Many animals exhibit different social structures during non-breeding and breeding periods, but we know little about the environmental factors associated with when these shifts in social structure occur. Here, we show that photoperiod and rainfall, two environmental variables commonly associated with the development of breeding physiological phenotypes, are also associated with the timing of shifts from non-breeding to breeding social structure in the Red-backed Fairywren ( Malurus melanocephalus ), a small Australian songbird.